Total dose effect of Al2O3-based metal–oxide–semiconductor structures and its mechanism under gamma-ray irradiation. (11th October 2018) - Zhu, H P; Zheng, Z S; Li, B; Li, B H; Zhang, G P; Li, D L; Gao, J T; Yang, L; Cui, Y; Liang, C P; Luo, J J; Han, Z S
Abstract: In our work, insights into the total dose response and native point defect behavior in the Al2 O3 gate dielectric during irradiation were gained by gamma-ray irradiation experiments and first-principles calculations. It is found that the O vacancy (VO ) can act as a hole trap in the Al2 O3 gate dielectric during irradiation, leading to the negative shift of the capacitance–voltage ( C–V ) curves of the Al2 O3 -based metal–oxide–semiconductor (MOS) structure. Our calculations show that the neutral defect VO becomes a +2 charged center after irradiation, and the positively charged VO is a kind of conductive path for electrons, which contributes to an increase of the leakage current in the irradiated MOS capacitors. Additionally, the trapped holes are accumulated with irradiation doses, which can lower the barrier height of the Al2 O3 gate oxide and further cause the increase of the leakage current. The other native point defects in the Al2 O3 layer, such as aluminum vacancy (VAl ), aluminum interstitial (Ali ) and oxygen interstitial (Oi ), only act as fixed charge centers during irradiation. Net negative charges existing in the Al2 O3 layers before irradiation are mainly induced by the negatively charged defects of VAl and Oi .